2015
DOI: 10.1097/ypg.0000000000000077
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and association of brain-derived neurotrophic factor (BDNF) gene with obsessive-compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) is a severe psychiatric condition with a clear genetic component (Nicolini et al., 2009) in which neurodevelopmental mechanisms may be etiologically important. Brain-derived neurotrophic factor (BDNF) is an interesting candidate for molecular analysis in OCD on the basis of potential functional relevance, positive association studies, and reported interaction between this gene and other neurotransmitters implicated in this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…This is the first association study between the BDNF Val66Met polymorphism and OCD conducted on a Japanese population. Our finding is consistent with the results of two meta-analyses of previous genetic association studies 21 , 29 and with the results of two genome-wide association studies. 30 , 31 Zai et al conducted a meta-analysis of 13 genetic association studies (five family-based association studies and eight case–control studies, which included Caucasian, Turk, Mexican, and South African Afrikaner cohorts), and they found no association between the BDNF Val66Met polymorphism and OCD (allele OR, 1.09; 95% CI, 0.99–1.21; P =0.09).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is the first association study between the BDNF Val66Met polymorphism and OCD conducted on a Japanese population. Our finding is consistent with the results of two meta-analyses of previous genetic association studies 21 , 29 and with the results of two genome-wide association studies. 30 , 31 Zai et al conducted a meta-analysis of 13 genetic association studies (five family-based association studies and eight case–control studies, which included Caucasian, Turk, Mexican, and South African Afrikaner cohorts), and they found no association between the BDNF Val66Met polymorphism and OCD (allele OR, 1.09; 95% CI, 0.99–1.21; P =0.09).…”
Section: Discussionsupporting
confidence: 92%
“… 30 , 31 Zai et al conducted a meta-analysis of 13 genetic association studies (five family-based association studies and eight case–control studies, which included Caucasian, Turk, Mexican, and South African Afrikaner cohorts), and they found no association between the BDNF Val66Met polymorphism and OCD (allele OR, 1.09; 95% CI, 0.99–1.21; P =0.09). 21 Mattheisen et al conducted a genome-wide association studies (N=5,061), and they did not find the BDNF Val66Met polymorphism among the top 33 single-nucleotide polymorphisms (SNPs) with P <1×10 −5 . 30 However, caution must be exercised, because the sample size of each association study, including our study, was small, and the allele frequency of this polymorphism is dependent on ethnic background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (33,34) have found significant ethnic differences of the BDNF Val66Met polymorphism frequencies, with an approximate Met allele frequency 40% in Eastern and 20% in Western. In order to clarify whether OCD susceptibility is correlated with the ethnic differences of the Val66Met polymorphism, we performed subgroup analyses by ethnicity.…”
Section: Discussionmentioning
confidence: 98%
“…• There was a significant relationship between the TT genotype of BDNF val66Met polymorphism in OCD. [32,33], i.e. expressed in the brain tissue.…”
Section: O Highlightsmentioning
confidence: 99%